Kesalahan Tanda Baca Pada Hasil Tugas Siswa Dalam Materi Teks Eksplanasi Kelas XI Jurusan TKJ SMK Taman Madya Baiturrahman Bima - Subhan, Subhan; Haris, A.; Arwan, Arwan; Fadli, Bagus Muhammad (Universitas Pahlawan Tuanku Tambusai, 2025)
Punctuation errors in the results of student assignments at SMK Taman Madya Baiturrahman Bima are often found. These errors are reviewed to see the underlying factors. Based on that, the objectives of this study are 1) to describe the forms of punctuation errors in the results of student assignments in the explanatory text material for class XI TKJ Department of SMK Taman Madya Baiturrahman Bima, and 2) to examine the factors that influence punctuation errors in the results of student assignments in the explanatory text material for class XI TKJ Department of SMK Taman Madya Baiturrahman Bima. This study is a qualitative study using a qualitative descriptive method. The data for this study are sentences related to punctuation errors. The data source comes from teachers and students of class XI TKJ Department at SMK Taman Madya Baiturrahman Bima. The data collection techniques used are observation, assignments, interviews, and documentation. The data analysis technique for this study uses descriptive analysis techniques. The results of this study are (1) the forms of punctuation errors in the explanatory text assignments of class XI students majoring in Computer and Network Engineering at SMK Taman Madya Baiturrahman Bima include period punctuation, comma punctuation, colon punctuation, and hyphen; (2) the factors that influence punctuation errors in the explanatory text assignments of class XI students majoring in Computer and Network Engineering at SMK Taman Madya Baiturrahman Bima are caused by low student interest and motivation towards learning, varying levels of student cognitive ability, different student memories, lack of student understanding regarding punctuation, the surrounding environment that does not support learning, complicated teacher explanations, lack of time in learning, students' habits of not paying attention during learning, students' lack of self-confidence, and lack of student accuracy in placing punctuation.